Detecting Mediterranean White Sharks with Environmental DNA - Jeremy Jenrette; Jennifer Jenrette; Kobun Truelove; Stefano Moro; Nick Dunn; Taylor Chapple; Austin Gallagher; Chiara Gambardella; Robert Schallert; Brendan Shea; David Curnick; Barbara Block; et al. (Oceanography, 2023)
The white shark (Carcharodon carcharias) is a globally distributed, ecologically important top predator whose biology and population dynamics are challenging to study. Basic biological parameters remain virtually unknown in the Mediterranean Sea due to its historically low population density, dwindling population size, and lack of substantial sightings. White sharks are considered Critically Endangered in the Mediterranean Sea, and recent analyses suggest that the population has declined by 52% to 96% from historical levels in different Mediterranean sectors (Moro et al., 2020). Thus, white shark sightings dating back to 1860 are being used to estimate population trajectories throughout the entire region. Though the population size is unknown, remaining individuals are thought to be primarily restricted to a handful of hotspots deemed important for their reproduction and foraging. One of these hypothesized hotspots is the Sicilian Channel, which accounts for 19% of total historical sightings.